2017
DOI: 10.1002/anie.201708484
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Proof of the Bifunctional Mechanism for the Hydrogen Oxidation in Alkaline Media

Abstract: Realization of the hydrogen economy relies on effective hydrogen production, storage, and utilization. The slow kinetics of hydrogen evolution and oxidation reaction (HER/HOR) in alkaline media limits many practical applications involving hydrogen generation and utilization, and how to overcome this fundamental limitation remains debatable. Here we present a kinetic study of the HOR on representative catalytic systems in alkaline media. Electrochemical measurements show that the HOR rate of Pt-Ru/C and Ru/C sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
238
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(272 citation statements)
references
References 31 publications
(25 reference statements)
15
238
0
1
Order By: Relevance
“…The positive effect of the surface pre-oxidation on theNi catalytic activity in HOR was also reported previously[52,63]. This observation might serve as a direct experimental evidence of the bifunctional mechanism of HOR[26,50,[64][65][66][67], when OHad species, pre-chemisorbed on the adjacent active sites, are required in order to remove Had chemisorbed on the free metallic surface of Ni, and to make the hydrogen oxidation reaction proceed.Thus, presumably a certain optimal ratio of Ni(OHad)/Ni(Had) sites is needed to retain the HOR activity of bare Ni electrocatalyst. Therefore, the theoretical estimations of HBE and OHBE, provided inFigure 1, (a)and (b), might shed some light on the understanding of the competitive co-adsorption of H and OH species (see section 2.1).…”
supporting
confidence: 83%
“…The positive effect of the surface pre-oxidation on theNi catalytic activity in HOR was also reported previously[52,63]. This observation might serve as a direct experimental evidence of the bifunctional mechanism of HOR[26,50,[64][65][66][67], when OHad species, pre-chemisorbed on the adjacent active sites, are required in order to remove Had chemisorbed on the free metallic surface of Ni, and to make the hydrogen oxidation reaction proceed.Thus, presumably a certain optimal ratio of Ni(OHad)/Ni(Had) sites is needed to retain the HOR activity of bare Ni electrocatalyst. Therefore, the theoretical estimations of HBE and OHBE, provided inFigure 1, (a)and (b), might shed some light on the understanding of the competitive co-adsorption of H and OH species (see section 2.1).…”
supporting
confidence: 83%
“…Thus, the synergistic ligand and strain effect of Au incorporation weakening hydrogen adsorption over Pt atom benefits the oxidative desorption of surface hydrogen (Volmer step: H ad + OH − → H 2 O + e − ) and consequently improves HOR activity in alkaline media [38] . Other than H adsorption on Pt sites, recent studies revealed that the adsorbed OH ads also plays an important role in HOR through the so-called bifunctional mechanism [28,39] . The CV for the adsorption/desorption of OH is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…E-mail addresses: huangxun@cqu.edu.cn (X. Huang), zdwei@cqu.edu.cn (Z. Wei). electrochemical reactions such as O 2 reduction reaction [25] , methanol oxidation [26] , hydrogen evolution [27] , organics oxidation reaction [28] and HOR [29] . However, the rationale for the expected improvement in both activity and kinetics with the AuPt materials in alkaline media is still a matter of controversy [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Andere Arbeitsgruppen zogen die gleiche Schlussfolgerung gestützt auf Pt‐Ru‐Nanopartikel und Pt‐Nanodrähte, die mit anderen Übergangsmetallen legiert sind . Eine Kombination elektrochemischer und In‐situ‐spektroskopischer Resultate zeigte allerdings, dass die Gegenwart von OH‐Gruppen an den Ru‐Oberflächenzentren von Ru/Pt‐Legierungen eine wesentliche Rolle bei der Förderung des geschwindigkeitsbestimmenden Volmer‐Schritts in der HOR besitzt …”
Section: Zusammenstellung Theoretischer Und Experimenteller Studien Dunclassified